Thoracic aorta to inferior mesenteric artery bypass for treatment of chronic mesenteric ischemia - Marjorie R. Liggett; Margaret A. Reilly; Nidhi Reddy; Nicholas S. Lysak; Heron Rodriguez; Neel A. Mansukhani (Annals of Vascular Surgery - Brief Reports and Innovations)
Despite the prevalence of mesenteric artery occlusive disease in the elderly population, revascularization for chronic mesenteric ischemia (CMI) accounts for <2 % of revascularization procedures. We describe a case of a 72-year-old male with CMI who previously underwent SMA angioplasty and stenting, and supraceliac aorta to superior mesenteric artery (SMA) bypass that subsequently thrombosed. We performed a right common iliac to SMA bypass with initial improvement in his symptoms. However, at one month follow-up, he had symptom recurrence with imaging revealing occlusion of his bypass. We subsequently performed a distal thoracic aorta to inferior mesenteric artery (IMA) bypass via a thoracoabdominal retroperitoneal approach, resulting in resolution of his symptoms.